UNGKAPAN MAKIAN DALAM BAHASA MELAYU BENGKULU ANALISIS MAKNA DAN KONTEKS SOSIAL - Maria Botifar (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
This research aimed at finding out the semantic and social context of invective expressions in Bengkulu Malay Language. The data was taken from four families in Bengkulu Malay society by using observation, interview, and field notes techniques. The result shows that there are thirty invective expressions in Bengkulu Malay Language which are grouped into four categories: parts of body, intellectuality, disease, and behavior category. Contextually, invective expressions belong to negative semantic. Textually, those expressions belong to neutral semantic. It is due to the associations which encompass the expressions. Based on social context, there are some factors need to be considered in speech. They are: 1) kinship, superior-inferior, and social aloofness; 2) emotional state of the speaker; and 3) the scene in which the speech take place, including the place, time, and the act.